2012
DOI: 10.1002/lary.23409
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of whole body positron emission tomography (PET)/PET‐computed tomography and conventional anatomic imaging for detecting distant malignancies in patients with head and neck cancer: A meta‐analysis

Abstract: Compared with conventional anatomic imaging, whole body PET/PET-CT has excellent diagnostic performance for detecting distant malignancies in patients with head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Determining the presence or absence of extracapsular invasion is of importance; therefore, thin slice CT or MRI assists in an accurate evaluation. 18 Fluorodeoxyglucose (FDG) positron-emission topography (PET) exhibits high accuracy for tumor involvement [ 29 ] and can be used to screen for distant metastasis [ 30 ]. FDG-PET scans may be recommended especially in the case of advanced disease.…”
Section: Clinical Work-upmentioning
confidence: 99%
“…Determining the presence or absence of extracapsular invasion is of importance; therefore, thin slice CT or MRI assists in an accurate evaluation. 18 Fluorodeoxyglucose (FDG) positron-emission topography (PET) exhibits high accuracy for tumor involvement [ 29 ] and can be used to screen for distant metastasis [ 30 ]. FDG-PET scans may be recommended especially in the case of advanced disease.…”
Section: Clinical Work-upmentioning
confidence: 99%
“…the most important diagnostic procedure and standard to screen for distant metastases in HNSCC is a Ct scan of the thorax to evaluate for pulmonal and mediastinal lesions [19]. Some authors suggest the use of positron emission tomography to increase sensitivity in screening for distant metastasis [19][20][21]. However, this technique has not become a routine practice in many centers yet, as clear data on its predominance over conventional methods are pending and its use is cost-intensive and access often limited.…”
Section: Preventive Measuresmentioning
confidence: 99%
“…Chest CT is regarded as the single most important technique for diagnosis of distant malignancies in patients with HNSCC . In the past 10 years, 18 F‐fluorodeoxyglucose (FDG) positron emission tomography (PET) has played an important role in oncology, especially for evaluating distant metastases in patients with HNSCC . From a meta‐analysis from 4 directly compared studies (377 patients), 18 FDG PET showed higher sensitivity (85% vs 62%) than chest CT .…”
Section: Introductionmentioning
confidence: 99%